Effects of visible light radiation on macrophyte litter degradation and nutrient release in water samples from a eutrophic shallow lake. Issue 10 (25th November 2016) - Liu, Xin; Huang, Qing-Hui; Jiang, He-Long; Song, Na
ABSTRACT: Visible light is a major fraction of the solar spectrum; however, information on visible light radiation of macrophyte detritus is lacking. In this study, we conducted a microcosm experiment to assess the effects of visible light radiation on degradation of two litter species: Potamogeton malaianus ( P. malaianus ) and Phragmites australis ( Ph. australis ). This research represents an investigation of mass loss, microbial activity and nutrients released over a period of 168 days. Overall, we found that visible light radiation had significant effects on litter decomposition, but it did not affect the microbial activities which degrade cellulose and lignin. The decomposition rate order of the three components in P. malaianus and Ph. australis in treatments was: cellulose > hemicellulose > lignin. The visible light radiation mainly affected the degradation of lignin, which is the primary compound in litter susceptible to photodegradation. The exposure to visible light radiation up to 17.6 Wm −2 stimulated the dissolved organic carbon release and reduced the molecular weight to less reactive. Meanwhile, no obvious difference in nutrient contents (TP, TN, NO3 –N, NO2 –N, and NH3 –N) was observed among different visible light intensities. The results of this study contribute to better understanding of the photochemical behaviour of macrophyte litter in shallow lakes.